Individual Counseling Services Based on REBT to Handle Student Victims of Bullying at Islamic State Junior High School 1 Banyumas - Falia Nurarviani; Vici Prihmaningrum AM; Umi Haniati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The phenomenon of bullying has become a spotlight because it is considered a serious problem that occurs in many schools. This bullying is often experienced by teenagers and can have a negative impact on the psychological condition of the victim. This study uses a qualitative descriptive method with a case study research type. Data are collected through observation, interviews, and documentation. The purpose of this study was to determine the impact of bullying experienced by a grade VII student at Islamic State Junior High School 1 Banyumas and to identify the stages of individual counseling services using the Rational Emotive Behavior Therapy (REBT) approach to help students who are victims of bullying. The results showed that students who were victims of bullying experienced psychological impacts such as a lack of self-confidence, feeling anxious while at school, and preferring to be alone. To address these problems, BK teachers provide individual counseling using the REBT approach. Individual counseling services using the REBT approach consist of 3 stages: the initial stage (identification of irrational thoughts), the working stage (disputation or refutation of irrational thoughts), and the final stage (replacement with more rational thoughts). These findings suggest that individual counseling services with the REBT approach can help students who are victims of bullying to rebuild their self-confidence, think more positively, and accept themselves better. Keywords: bullying, individual counseling, rational emotive behavior therapy